Workplace violence in the ambulance service from the offender’s perspective: a qualitative study using trial transcripts - Magnus Viking; Karin Hugelius; Erik Höglund; Lisa Kurland (BMC Emergency Medicine)
Abstract Background Workplace violence is a widely recognised problem within the ambulance service context. The causes of workplace violence have often been attributed to patient- or situation-related risk factors. However, there is a lack of research on workplace violence from the offender’s perspective. Aim To explore workplace violence directed toward ambulance services from the offender’s perspective. Methods An explorative qualitative study was conducted using inductive thematic analysis of trial transcripts from cases tried in court between 2013 and 2023. Plaintiffs in these cases were ambulance personnel or the ambulance service itself. Offenders were those convicted of committing or attempting any of the following acts: threats, theft, assault, molestation or murder. Results Twenty-three trial transcripts were analysed, and four themes were found: (I) the offender was misunderstood, which included communication problems and other misunderstandings; (II) the offender was disrespected, which described perceived unprofessional behaviour and unpleasant or painful treatment by ambulance personnel; (III) the offender was vulnerable, which described the state of the offender (i.e., being under the influence of alcohol or drugs); and (IV) the offender had unmet expectations, which included perceived unreasonable waiting time and conflicting expectations of ambulance care. Conclusion The analysis of trial transcripts revealed four themes from the offender perspective: feelings of being misunderstood, disrespected, vulnerable, and having unmet expectations. It is important to view these results critically, as they are based on trial transcripts in which the offender was found guilty of a crime and may have been attempting to defend his or her actions during the trial. Despite this caveat, healthcare professionals need also to recognise that their behaviour may influence the risk of workplace violence. This knowledge can be harnessed to develop training programs for ambulance personnel.